Ototoxicity monitoring through the eyes of the treating physician: Perspectives from pulmonology and medical oncology. (24th August 2018) - Garinis, Angela C.; Cornell, Alexandra; Allada, Gopal; Fennelly, Kevin P.; Maggiore, Ronald J.; Konrad-Martin, Dawn
Abstract: Objectives : Integrating audiological management into the care pathways of clinical specialties that prescribe ototoxic medications for essential, often life-preserving medical care that is critical for early hearing loss identification and remediation. Research shows that successful implementation of a new health service or intervention requires alignment of goals among provider groups, institutional leadership and patients. Thoughtful consideration of the physician's viewpoints about ototoxicity and its implications for treatment planning is, therefore, important for the implementation and enduring success of an ototoxicity monitoring programme (OMP). Design : This discussion paper uses qualitative methods to explore the perspectives of four physicians on OMP provision in their patient populations. Study sample : Three pulmonologists and one oncologist completed the written survey or survey-based interview described in this report. Results : Each physician indicated that (i) ototoxicity is a potential problem for their patients; (ii) monitoring hearing is important to ensure good quality of life among their patients and (iii) treatment modification would be considered if an alternative treatment option were available. The physicians differed in their approaches to ototoxicity monitoring, from routine referrals to audiology, to relying on patient self-referral. Conclusion : Physician provider input is needed to optimise monitoring schedules and OMP care coordination with audiology.